Просим к столу: [сокращенный перевод с латышского] / Н. П. Масилюне - Масилюне Нина Петровна (Авотс, 1985)
Экземпляры: КХ (20240522) / Инвентарный номер: 851538 / Сис.шифр: 641 / Авт.знак: М 31 / ГРНТИ: 65 / ББК: 36